2019
DOI: 10.1371/journal.pntd.0007335
|View full text |Cite
|
Sign up to set email alerts
|

Genetic landscape and macro-evolution of co-circulating Coxsackieviruses A and Vaccine-derived Polioviruses in the Democratic Republic of Congo, 2008-2013

Abstract: Enteroviruses (EVs) are among the most common viruses infecting humans worldwide but only a few Non-Polio Enterovirus (NPEV) isolates have been characterized in the Democratic Republic of Congo (DR Congo). Moreover, circulating vaccine-derived polioviruses (PVs) [cVDPVs] isolated during multiple outbreaks in DR Congo from 2004 to 2018 have been characterized so far only by the sequences of their VP1 capsid coding gene. This study was carried to i) investigate the circulation and genetic diversity of NPEV and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
(129 reference statements)
1
10
0
Order By: Relevance
“…Although discordant in terms of prevalence, these results are concordant with previous studies reporting the circulation of a wide range of enteroviruses in both humans and great ape populations from different African countries and elsewhere [ 16 , 19 , 20 , 22 , 40 , 41 , 42 , 43 ]. Interestingly, the strains and amplified genome fragments from all territories and from humans and NHPs are almost identical.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although discordant in terms of prevalence, these results are concordant with previous studies reporting the circulation of a wide range of enteroviruses in both humans and great ape populations from different African countries and elsewhere [ 16 , 19 , 20 , 22 , 40 , 41 , 42 , 43 ]. Interestingly, the strains and amplified genome fragments from all territories and from humans and NHPs are almost identical.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, no recombination events were observed with the genome sequences of strains CV-A13 (DQ995644) and PV3 (KY941933). Based on data from the cVDPV literature in outbreak regions, such as Cambodia, Madagascar, Democratic Congo and Nigeria, CV-A, including CV-A13, CV-A17, CV-A20 and CV-A11, have been reported as partners most frequently involved in recombination with PV strains [ 14 , 16 , 41 , 46 , 49 , 51 ]. In addition to infecting humans and being enteroviruses of human origin, CV-A has also been found in NHPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, none of the most common EV types circulating among humans in Central Africa (CV-A13, EV-C99, CV-A20, CV-A24, CV-Bs or echoviruses of diverse types [11, 14, 51]) was detected in the panels of NHP stools in which EV-D111 and EV-D120 were found. Yet, NHPs are susceptible to many types of human EVs, as observed in several occasions [45, 46, 5255].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are 112 gene sequences in the GenBank database, associated with various clinical manifestations including AFP ( Oberste et al, 2004 ; Bingjun et al, 2008 ; Rao et al, 2012 ; Laxmivandana et al, 2013 ; Sadeuh-Mba et al, 2013 ; Tao et al, 2014a ; Fernandez-Garcia et al, 2017 ; Maan et al, 2019 ; Sadeuh-Mba et al, 2019 ) (47 isolates worldwide), aseptic meningitis ( Avellon et al, 2006 ) (8 isolates in Spain, 2005), encephalitis ( Lewthwaite et al, 2010 ; Kumar et al, 2012 ) (13 isolates in India, 2006–2010), diarrhea ( Rao et al, 2013 ; Patil et al, 2015 ) (7 isolates in India, 2005–2011), respiratory diseases ( Opanda et al, 2016 ; Hellferscee et al, 2017 ) (5 isolates in total), and others ( Oberste et al, 2004 ) ( Figure 1 ). With the addition of the seven Tibetan EV-B75 isolates from this study, no significant or typical temporal and spatial aggregation of EV-B75 was observed worldwide.…”
Section: Resultsmentioning
confidence: 99%